Tempo, semiose e cultura: uma visão sistêmica sobre os processos de criação no design gráfico brasileiro - Silveira, Isabel Orestes (2010)
This thesis aims at scrutinizing the creative process of the Brazilian graphic design. The perspective from which it will be done comprises three cases, with the different and the common creative procedures being underlined in the text, based on the interviews made with some different designers. In these cases, a paradox between economy and culture can be seen, showcasing the creation of the abovementioned professionals and, at the same time, highlighting the limits that submit the creation to the market rules. The intention here is to describe the non-linearity of thought, which experiences diverse temporality when making projects. Thus, considering the variables that relate time to the creative process, how can we comprehend the procedures and acts of the graphic designers within this sort of temporality? The hypothesis suggests two directions: first of all, this research examines the relationship between design and culture from the perspective of Pinheiro (2007) and Lotman (1898; 1996), understanding the designer as a translator of visual signs. Secondly, it must not fall into oblivion that there is a multitude of times , internalizing the conscious, which impel the designers to make projects in the context of the creative process. A retrospective study of the past was done based on Braudel (1987), who is a historiographer specialized in the permanence in the long time . This research revolves around the idea that, independently of the object taken as the center of an investigation, it is more what happens during the creative process that defines the complexity as a principle of work (MORIN, 2006). The time leads the variables of the process to the dimension of an open model, which simply does not reject the doubt. This instability and, to some extent, this chaos follow the ideas of Eco (2005) and Prigogine (1996), both of whom discuss the principles of uncertainty and self-organization, which prevent the unstable systems from keeping themselves on the way of the entropy. Then, it is necessary to reach a probabilistic description of the object of this study in the light of General System Theory (GST) and Vieira (2008). These possibilities convey an universe where everything is stream and changing. The fundamentals of the creative process based on semiotics have in Salles (2006) the trinity that follows: the complexity of the systems, the temporality of the creative process and the representation of the graphic designers